Pengaruh Suasana Toko (Store Atmosphere) Terhadap Minat Beli Konsumen Pada Toko “Amel” Bungamas Kikim Timur - Rudi Eduar (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2021)
The purpose of this study was to determine the effect and relationship to Store Atmosphere on consumer buying interest on AMEL Store, East Kikim Sub distrik, Lahat District. The population in this study are all customers coming to the store and, the sampling technique in this study was done by using accidental sampling in the range of May-August 2020 as a sample of 50 consumers. The results of the analysis using SPSS version 19 show that: (1) the result of the regression equation Y = 2,589 + 0,244X + e. thus variable Store Atmosphere a positive influence on consumer buying. (2) The value of a correlation of 0.801, which means the correlation is very strong because it is on the criteria> 0,75- 0,99. (3) The value of R Square is 0.592, indicating that 59,2% Interest in Purchase can be explained by Store Atmosphere. From the t-test is known to have variable X t = 8,338 with t table = 1.677. So tcount> t table (8,338 > 1.677), so the variable Store Atmosphere (X) has a significant influence on the variable interest purchase (Y). So we can conclude this hypothesis is accepted, that the Store Atmosphere has a positive and significant impact on the Interest Purchase in AMEL Store, It has been expected AMEL Store can continue to explore these other factors in order to increase buying interest in accordance with the tastes of consumers.